Drug-induced sarcoidosis-like reaction in adjuvant immunotherapy: Increased rate and mimicker of metastasis. (May 2020) - Chorti, Eleftheria; Kanaki, Theodora; Zimmer, Lisa; Hadaschik, Eva; Ugurel, Selma; Gratsias, Emmanouil; Roesch, Alexander; Bonella, Francesco; Wessendorf, Thomas E.; Wälscher, Julia; Theegarten, Dirk; Schadendorf, Dirk; et al.
Abstract: Background: Anti-[programmed cell death protein 1 (PD-1)] antibodies nivolumab and pembrolizumab were approved for adjuvant treatment of melanoma as they demonstrated improved relapse-free survival. Currently, combined anti-PD-1 plus anti-[cytotoxic T-lymphocyte-associated protein 4 (CTLA4)] blockade is being investigated in adjuvant and neoadjuvant trials. Sarcoidosis-like reactions have been described for immune checkpoint inhibitors and are most likely drug-induced. The reported rate of sarcoidosis/sarcoidosis-like reactions within clinical melanoma trials is <2%. We observed that a remarkably higher number of melanoma patients (10/45 patients, 22%) treated with immune checkpoint inhibitor (ICI) within an adjuvant clinical trial-developed drug induced sarcoidosis-like reaction (DISR) mimicking metastasis. Case presentation: Of 45 stage III melanoma patients who were treated at our institute with adjuvant ICI (either nivolumab alone or in combination with ipilimumab) within a two-armed, blinded clinical trial, ten developed a DISR. Three of the ten patients were men, median age was 52 years (range, 32–70 years). DISRs were asymptomatic and generally detected radiographically at first radiographic imaging after the start of therapy (median time, 2.8 months) and described as a differential diagnosis to tumour progression. In one patient, DISR was only apparent 13.1 months after start of therapy and 4 weeks after the end of ICI treatment. DISR presented as mediastinal/hilar lymphadenopathy in 8/10 patients (as only site or in addition to lung, skin and/or bone involvement), one patient had only lung and cutaneous, one patient only cutaneous DISR. Biopsies from lymph nodes, skin and bone were taken in 8/10 patients, and histology confirmed sarcoidosis-like reactions (SLRs). As patients were asymptomatic, no treatment for DISR was required, and study treatment was stopped for DISR in only one patient due to bone involvement. DISRs have resolved or are in remission in all patients. At a median follow-up time of 15.3 months (range, 12–17.6 months), two patients experienced melanoma relapse. Conclusions: In most cases, sarcoidosis could only be differentiated from melanoma progression on biopsy. Treating physicians as well as radiologists have to be aware of the potentially higher rate of DISR in patients receiving adjuvant ICI. A thorough interdisciplinary workup is required to discriminate from true melanoma progression and to decide on continuation of adjuvant ICI treatment. Highlights: Potentially higher rate of sarcoidosis-like reactions (SLR) in patients who receive adjuvant immunotherapy than in patients with metastatic disease. Differentiation between SLR and progression of disease in most cases only possible with biopsy. No clinical symptoms of the SLR in our patients, no steroid treatment required. No progression of the SLR after continuation of treatment. Patients that developed SLR and patients that did not had an equal relapse rate (20%).